Bridging Unilamellar Nanosheets for High Performance Additive‐Free Supercapacitor Electrodes. Issue 13 (4th April 2016) - Gu, Feng; Cheng, Xing; Li, Tao; Lee, Pooi See
Abstract : Conductive Co(OH)2 nanoporous electrode is developed by topochemically bridging unilamellar nanosheets with in situ formed coordination bonds. The high electrical conductivity and ligand‐bridged nanoporous architecture endow the additive‐free Co(OH)2 electrode with excellent capacitance, rate capability and an impressive cycling stability.